2017
DOI: 10.21037/gs.2017.06.11
|View full text |Cite
|
Sign up to set email alerts
|

Central round block repair of large breast resection defects: oncologic and aesthetic outcomes

Abstract: Central round block reconstruction of large defects after WLE is a safe technique with good aesthetic outcomes. Contralateral symmetrising surgery is not usually required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In this context, it is crucial to establish a careful selection of patients who can be potentially submitted to conservative management, based on disease location, glandular or fatty volume composition, and breast size, always doing measurements regarding symmetry and ptosis degree [ 20 ]. Furthermore, the aim to maintain a good cosmetic result is directly linked to a wide excision with radical margins and being able to prevent local recurrences or disease progression [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is crucial to establish a careful selection of patients who can be potentially submitted to conservative management, based on disease location, glandular or fatty volume composition, and breast size, always doing measurements regarding symmetry and ptosis degree [ 20 ]. Furthermore, the aim to maintain a good cosmetic result is directly linked to a wide excision with radical margins and being able to prevent local recurrences or disease progression [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the overall percentage of seroma from pooled data was 6.5% (95% CI: 3.7%-11.4%). The highest percentage (28.6%) was reported by Bramhall et al, [17] .…”
Section: Discussionmentioning
confidence: 78%
“…The overall percentage of wound dehiscence/ delayed wound healing from pooled data is 3.3% (95% CI: 2.2%-5.1%). Only four studies reported that complication Bramhall et al [17] , Mohsen et al [10] , Refaat et al, [21] and Kyung In et al [14] the highest among them was Mohsen et al [10] with a percentage of 6.7%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Oncoplastic surgery increases the indication for BCS in case of large tumors or tumors at difficult locations of the breast, making it possible to obtain better cosmetic results and adequate surgical margins 1,2,7,10 . Tumors located at the upper quadrants can be excised and repaired by different oncoplastic techniques, including glandular reshaping or undermining, inferior pedicle mammaplasty 21 , round-block 22 , racket resection 7,23 , batwing technique 24 , among others. The main issues of all these techniques are repositioning the areola at the center of the new breast and avoiding a filling defect due to insufficient tissue after reshaping.…”
Section: Discussionmentioning
confidence: 99%